Molecular dynamics study of deformation mechanism of interfacial microzone of Cu/Al2Cu/Al composites under tension - Chen Yao; Wang Aiqin; Guo Zishuo; Xie Jingpei (Nanotechnology Reviews, 2022)
The micromechanical behavior of an Al/Al2Cu/Cu multilayer with characteristic crystal orientation during uniaxial tensile deformation was investigated by molecular dynamics. The simulation results showed that under tensile loading, the dislocation nucleates at the Cu/Al2Cu heterogeneous interface and moves toward the Cu layer along the {111} crystal plane. The deformation mechanism is intralayer confinement slip. As the dislocations proliferated, interactions between them occurred; resulting in the formation of insertion stacking faults and deformation twins in the Cu and Al layers. However, no dislocation lines were generated in the Al2Cu layer during tensile deformation. As the load increased, the stress concentration at the Al2Cu/Al interface led to the fracture of the complex. In addition, the microplastic deformation mechanism and mechanical properties of Al/Al2Cu/Cu composites at different temperatures and strain rates were significantly different. These results revealed the microdeformation mechanism of laminated composites containing brittle phases.